2020
DOI: 10.1021/acssuschemeng.0c02684
|View full text |Cite
|
Sign up to set email alerts
|

Neoteric Solvent Systems as Sustainable Media for Dissolution and Film Preparation of Poly-[(R)-3-hydroxybutyrate]

Abstract: Polyhydroxyalkanoates (PHAs) have a wide range of applicability due to their biodegradable and biocompatible characteristics. This makes them suitable for commercialization as an alternative to petroleum-based synthetic plastics. Solvents such as chloroform are reported to solubilize polyhydroxyalkanoates. With chloroform being hazardous for both health and the environment, this work attempts to replace this chlorinated solvent with green solvents like ionic liquids. In this study, poly-[(R)-3hydroxybutyrate] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The pot experiment showed that the growth of peanut seedlings covered with a blank PHB film was better than that of peanut seedlings without a PHB film cover ( Figure 12 ). The degradation of PHB has a certain nutritional effect on the growth of plants [ 29 ]. With the increase of PRO/PHB antifungal film content, the root length, fresh weight, and dry weight of peanut seedlings increased slightly and then decreased.…”
Section: Resultsmentioning
confidence: 99%
“…The pot experiment showed that the growth of peanut seedlings covered with a blank PHB film was better than that of peanut seedlings without a PHB film cover ( Figure 12 ). The degradation of PHB has a certain nutritional effect on the growth of plants [ 29 ]. With the increase of PRO/PHB antifungal film content, the root length, fresh weight, and dry weight of peanut seedlings increased slightly and then decreased.…”
Section: Resultsmentioning
confidence: 99%
“… Dubey et al, 2017 reported the extraction of PHA utilizing green solvents. Also, the dissolution of PHA was reported in green solvent diethanol ammonium acetate with maximum solubility of 3% w/v at 70°C ( Sequeira et al, 2020 ). Herein, the extracted polymer showed good thermal and mechanical properties compared to standard PHB from Sigma Aldrich.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, aqueous solutions of QASs were investigated for their ability to dissolve alginic acid. The cloud point method was used to determine the dissolution extent of alginic acid following the steps previously reported by us. , In a typical experiment, the dissolution efficiencies of the aqueous solutions of QASs were studied by adding desired amounts of alginic acid in each of them, first at room temperature (RT = 27 °C) and then gradually increasing temperature up to 70 °C (only for those solutions that showed insolubility at RT) with stirring under an atmosphere of nitrogen until a clear homogeneous solution is obtained. An optical microscope (100×) (Figure S1, Supporting Information) was used to observe the aliquots, and the absence of insoluble fibers of alginic acid with a gradual increase in reaction time in the respective solutions confirmed complete dissolution of the seaweed polysaccharide.…”
Section: Methodsmentioning
confidence: 99%
“…Total microbial load count in the presence of TMAA was done using soil bacteria following the method reported earlier by us. 33 Soil samples were collected from pot culture experiment sites of CSIR-CSMCRI. 1 g of TMAA was dissolved in 50 mL of distilled water (test sample).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%